Performance Optimization of Unglazed Nanofluid Photovoltaic/Thermal System: Energy and Exergy Analyses - M. Imtiaz Hussain; Jun-Tae Kim (International Journal of Photoenergy)
The focus of this paper is to predict the transient response of a nanoengineered photovoltaic thermal (PV/T) system in view of energy and exergy analyses. Instead of a circular-shaped receiver, a trapezoidal-shaped receiver is employed to increase heat transfer surface area with photovoltaic (PV) cells for improvement of heat extraction and thus achievement of a higher PV/T system efficiency. The dynamic mathematical model is developed using MATLAB® software by considering real-time heat transfer coefficients. The proposed model is validated with experimental data from a previous study. Negligible discrepancies were found between measured and predicted data. The validated model was further investigated in detail using different nanofluids by dispersing copper oxide (CuO) and aluminum oxide (Al2O3) in pure water. The overall performance of the nanoengineered PV/T system was compared to that of a PV/T system using water only, and optimal operating conditions were determined for maximum useful energy and exergy rates. The results indicated that the CuO/water nanofluid has a notable impact on the energy and exergy efficiencies of the PV/T system compared to that of Al2O3/water nanofluid and water only cases.